EKSPERIMENTASI PEMBELAJARAN MATEMATIKA DENGAN MODEL PROBLEM BASED LEARNING(PBL) DAN LEARNING CYCLE 5E DENGAN PENDEKATAN SAINTIFIK PADA MATERI DIMENSI TIGA DITINJAU DARI KEMANDIRIAN BELAJAR SISWA KELAS X SMA NEGERI DI-KABUPATEN SUKOHARJO - Paryatun, Suji; Usodo, Budi; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Abstract: The research aims to know: 1) which learning model is better achievement LC 5E with scientific appraoach, PBL, or direct learning models : 2) the learning autonomy category giving a better achievement among the high, medium, and low level of learning autonomy; 3) the learning autonomy which yields a better achievement of each learning model ; and 4) learning model which yields a better achievement of each learning autonomy category. The type of the research is a quasi-experimental research. The research is carried out in Sukoharjo regency. The populations of research are all 10th students of in Sukoharjo regency in which  school based curriculum applied in the academic year of 2014-2015. The sampling technique uses Stratified Cluster Random Sampling. The data collecting techniques use documents, questionnaires, and tests. The data analysis technique uses two-way variant analysis with unequal cells. The research concludes that; 1) the LC 5E learning model with scientific approach gives a better achievement in mathematics learning; 2) the students with high learning autonomy get better mathematics scores. The indicator is the average  scores of students with high learning autonomy are better than those with low or medium level; 3) In each learning model, the students with high learning autonomy get  better achievements than those  with medium or low as well  learning autonomy in general,whereas in high learning autonomy category, the LC 5E learning with scientific approach shows a better math achievement than PBL; and 4) For the classification of learning autonomy between the high level and the medium one,  learning model  LC 5E with scientific approach shows better achievement mathematics learning than the one with PBL  or direct learning, whereas, the low learning autonomy has no different achivement LC 5E with scientific approach, PBL or the direct one.Keywords: Mathematics Learning Achievement, Learning Autonomy, Learning Model